A Semiotico-Pragmatic Analysis of President Nana Addo Danquah Akufo-Addo’s Address on Ghanaian Economy - Israel, Peace Chinwendu; Dumfeh, Helena Asantewaa; Amakyewa, Jennifer Owiredu; Bekoe, Ebenezer (Advances in Social Sciences Research Journal, 2023)
This study analyzed President Nana Addo Dankwa Akufo-Addo first official address on the Ghanaian economic crisis. It is qualitative study and explicit content analytical method was employed. Applying concepts from semiotic model and pragmatic act, the study revealed different semiotic elements and practs through which the presidents effectively communicated to his audience on government’s plans and initiatives towards ameliorating the escalating inflation and the resultant economic hardship Ghanaians were experiencing. The findings revealed that semiotic elements such as the coat of arm, the president’s outfit, the national flag, the microphone and the outfit of the sign-language interpreter effectively acts as a signifier and immensely contributed to meaning. Again, the findings showed that the president employed several practs in his address such as informing (47.06%), tasking (13.37%), cautioning (7.45%), sympathizing and recounting (3.16%), promising (16.01%); pleading/praying, reporting, and instructing (2.11%) each, saluting (9.06%), suggesting and urging (1.05%) each. The paper therefore concludes that through shared situational knowledge, reference and inference, Ghanaians were able to understand what the president wishes to communicate.